ANALISA METALURGI KASUS KEGAGALAN PELAT LOGAM IMPLAN UNTUK FIKASI PATAH TULANG DAN PERBANDINGANNYA DENGAN LOGAM IMPLAN BARU - Rusrial Rusrial; Gunawarman Gunawarman (Jurnal Teknik Industri Terintegrasi, 2018)
Fractures are the result of pressure that exceeds the ability of bone to withstand the pressure. Principles of fracture treatment include reduction, immobilization, and restore normal function and strength with rehabilitation. Biomaterials is a material that is paired implants in the human body to sustain a broken bone repositioning. Current position to restore the bone to its original state is usually used as a metal plate fixation especially in the internal fixation. Stainless steel is one material that often is used as temporary fixation material and then released after bone connected. In this study, the test specimen is a commercial implant material that is widely used today, such as stainless steel 316L implant which is a material that has the properties of good corrosion resistance that can be accepted by the human body tissues. Stages of the manufacturing process of the specimen consists of the cutting process, the formation and establishment of gauge lenght. The results showed that the tensile strength of the material after the power failure as bone fixation is not much different with the new implant is a metal ± ± 165.8 MPa and 109.42 MPa. From this study, a material which has failed to have a higher tensile strength values ± 56.38 MPa of new metal implants. By looking at the results of microstructure observation can provide information about fault models, the size and number of the different structures. This commercial implant material or greater reduction in cross-sectional area along the cracks and going tug indicate resilient material used. Failures that occur due to the low tensile strength of the metal implants are used as fixation strength compared to standard steel material. low tensile strength is caused by the corrosion of the metal.